A narrativa histórica da superação do atraso: um desafio historiográfico do Espírito Santo - Nascimento, Rafael Cerqueira do (2016)
This thesis aims to perform a history of the historiography of Espírito Santo trying to understand the procedures, functions and meanings involving different historiographical productions about the state of Espírito Santo between the 1960s and the early twenty-first century. The research analyzes the books História do Estado do Espírito Santo, by José Teixeira de Oliveira (1975), História do Espírito Santo, by Maria Stella de Novaes (1964), O Espírito Santo é assim, by Neida Lúcia Borges (1971), and Gabriel Bittencourt’s História Geral e Econômica do Espírito Santo: do engenho colonial ao complexo fabril-portuário (2006). Besides these, it discusses a new historiography that emerges in the first decade of this century, specially, but not exclusively, associated to the Social History of Political Affairs Program (Programa de História Social das Relações Políticas – PPGHIS-UFES). Therefore, grounding the analysis on references of History of Historiography and Theory of History, in particular Reinhart Koselleck and Jörn Rüsen, this thesis evaluates which kind of relations the historiographical productions established with the local past and which meanings the historical narratives attributed to this past. Thus, on the one hand, we identify the emergence and course of a historical narrative of overcoming backwardness: the narrative of the progressive development of Espírito Santo, set in the works of José Teixeira de Oliveira, Neida Lucia and Maria Stella de Novaes, and account of the economic formation of Espírito Santo, represented by the work of Gabriel Bittencourt. On the other hand, we demonstrate how the new historiography, critical narratives about Espírito Santo, has collaborated with the deconstruction of those mainstream narratives about the past of state. We, therefore, consider that the analysis of this local history writing path allowed us to comprehend how this paradigm of writing and understanding the past of Espírito Santo was built on the notions of delay and overcoming. We understand that the perspective of overcoming the delay defined a place for periods, historical events and characters that had their value to the local past defined in terms of their contribution to or obstruction of the development of the state. Doing so, we identify how the narratives of overcoming backwardness support the development projects of Espírito Santo and contributed to its legitimacy, both in the 1960s with industrialization, as in the political uses of the past performed by the political discourse of Paul Hartung on the Third Development Cycle in the XXI century. Finally, we evaluate the importance of critical narratives in deconstructing the perspective of overcoming the delay and its relevance in the definition of different meanings to the history of Espírito Santo.